Standarisasi Parameter Spesifik Ekstrak Etanol Daun Jarak Pagar (Jatropha Curcas L) sebagai Vasorelaxan - Fahmi Sadik; Muhammad Zulfian A. Disi (Journal Syifa Sciences and Clinical Research, 2023)
Jarak pagar (Jatropha curcas L.) is traditionally used as a medicinal plant and can be used scientifically to treat various diseases based on the scientific results of herbal medicine. This study aims to prove that the ethanol extract of Jarak pagar leaves (Jatropha curcas L.) meets the specific parameters for extract standardization. The ethanol extract of Jarak pagar (Jatropha curcas L.) leaves was obtained by maceration method, and then the extract was observed for specific parameters, which included an organoleptic test, identification of chemical content, determination of water-soluble juice content, and ethanol-soluble juice content, as well as other tests to see the activity of Jatropha curcas as a vasorelaxant using experimental methods. The results and data of specific parameter characteristics show that the extract made has met the requirements of Indonesian Medical Materials, which means that the ethanol extract of Jatropha curcas leaves made has met the standards, and based on activity testing, it is known that Jarak pagar leaves (Jatropha curcas L.) have the same activity as Vasorelaxan.